Heavy metal toxicity in plants and the potential NO-releasing novel techniques as the impending mitigation alternatives - Pande, Anjali; Mun, Bong-Gyu; Methela, Nusrat Jahan; Rahim, Waqas; Lee, Da-Sol; Lee, Geun-Mo; Hong, Jeum Kyu; Hussain, Adil; Loake, Gary; Yun, Byung-Wook (Frontiers in Plant Science, 2022)
Environmental pollutants like heavy metals are toxic, persistent, and bioaccumulative in nature. Contamination of agricultural fields with heavy metals not only hampers the quality and yield of crops but also poses a serious threat to human health by entering the food chain. Plants generally cope with heavy metal stress by regulating their redox machinery. In this context, nitric oxide (NO) plays a potent role in combating heavy metal toxicity in plants. Studies have shown that the exogenous application of NO donors protects plants against the deleterious effects of heavy metals by enhancing their antioxidative defense system. Most of the studies have used sodium nitroprusside (SNP) as a NO donor for combating heavy metal stress despite the associated concerns related to cyanide release. Recently, NO-releasing nanoparticles have been tested for their efficacy in a few plants and other biomedical research applications suggesting their use as an alternative to chemical NO donors with the advantage of safe, slow and prolonged release of NO. This suggests that they may also serve as potential candidates in mitigating heavy metal stress in plants. Therefore, this review presents the role of NO, the application of chemical NO donors, potential advantages of NO-releasing nanoparticles, and other NO-release strategies in biomedical research that may be useful in mitigating heavy metal stress in plants.